Avatrombopag for the treatment of thrombocytopenia in children's patients following allogeneic hematopoietic stem-cell transplantation: A pilot study - Ruan, Yongsheng; Cao, Wei; Luo, Tingting; Liu, Xuan; Liu, Qiujun; Xiao, Yuhua; Wu, Cuiling; Xie, Danfeng; Ren, Yuqiong; Wu, Xuedong; Feng, Xiaoqin (Frontiers in Pediatrics, 2023)
Thrombocytopenia following allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a common and life-threatening complication. Thus, new prevention and treatment strategies for post-HSCT thrombocytopenia are urgently required. In recent studies, thrombopoietin receptor agonists (TPO-RA) for treating post-HSCT thrombocytopenia indicated efficiency and safety. The improved effect of post-HSCT thrombocytopenia in adults was found in the administration of avatrombopag which was a new TPO-RA. However, there was no relevant study in the children’s cohort. Herein, we retrospectively analyzed the effect of avatrombopag in post-HSCT thrombocytopenia in children. As a result, the overall response rate (ORR) and complete response rate (CRR) were 91% and 78%, respectively. Furthermore, both cumulative ORR and CRR were significantly lower in the poor graft function (PGF) / secondary failure of platelet recovery (SFPR) group compared to the engraftment-promotion group (86.7% vs. 100%, p=0.002 and 65.0% vs. 100%, p<0.001, respectively). Achieving OR required a median of 16 days in the PGF/SFPR group while 7 days in the engraftment-promotion group (p=0.003). Grade III-IV acute graft versus host disease and inadequate megakaryocytes were identified as risk factors of CRR only in univariate analysis (p=0.03 and p=0.01, respectively). No severe adverse events were documented. Conclusively, avatrombopag is an alternatively efficient and safe agent for treating post-HSCT thrombocytopenia in children.